Estudo de competência em informação dos alunos do curso de Administração Pública da EAD da UFMT - Loureiro, Carlos Roberto (2020)
To build knowledge in higher education, it requires a demand for academic work, this is done by constantly seeking informational materials, knowledge and research techniques from different sources of information. It will be up to the academic to deal with these materials, in several of their supports, digital or not. This causes many difficulties for the academic both in the search for informational sources and in their perception of their needs and understanding of their content and use of information respecting their ethical limits. The understanding of these difficulties on the part of academics and especially professionals who mediate information with their users, can bring great benefits in improving the provision of information services. We have a contingent in profusion in Distance Education, (DE), with each passing year, many of the students who seek this modality, find many difficulties in adapting because they feel neglected by those responsible. The search for bibliographic information largely reflects the quality of academic work. The academic must learn skills in the search for information, because he must always be dealing with information throughout his professional life or other demands. Preparing them for these challenges will result in better trained professionals with better performances in their professional lives in a globalized world of information. This research aimed to investigate the information literacy of DE students, to meet their academic research needs in the construction of their knowledge in undergraduate courses. In the expectation of gathering information in the study on the factors involved in the search for information by distance learning students and with the purpose of ascertaining a general reality in relation to the informational needs of these students, through some private data collected from some students of DE, a qualitative approach was used, using the inductive method, with data collection technique, the questionnaire. By analyzing the data, we observed a lack of skills in dealing with information on the part of the academic community of the Public Administration course at DE. This is an indication that it will be necessary to work on training the student in information literacy.